2013
DOI: 10.1007/s10482-013-9954-9
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial siderophores efficiently provide iron to iron-starved tomato plants in hydroponics culture

Abstract: Iron is one of the essential elements for a proper plant development. Providing plants with an accessible form of iron is crucial when it is scant or unavailable in soils. Chemical chelates are the only current alternative and are highly stable in soils, therefore, posing a threat to drinking water. The aim of this investigation was to quantify siderophores produced by two bacterial strains and to determine if these bacterial siderophores would palliate chlorotic symptoms of iron-starved tomato plants. For thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
12

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(102 citation statements)
references
References 41 publications
4
80
0
12
Order By: Relevance
“…The use of cyclic AMP (cAMP), N-butyryl homoserine lactone, or N-oxohexanoyl-DL-homoserine lactone at a low concentration of 10 M permitted an increase in the microbial recovery of heterotrophic bacteria from the central Baltic Sea (146). The concept of mutualism between bacterial species emerged and was significantly highlighted by the role of siderophores (147)(148)(149). D'Onofrio et al identified 5 new acyldesferrioxamine siderophores isolated from Micrococcus luteus KLE1011, permitting the culture of a substantial number of marine bacterial species previously considered to be uncultivable (147).…”
Section: Signaling Compoundsmentioning
confidence: 99%
“…The use of cyclic AMP (cAMP), N-butyryl homoserine lactone, or N-oxohexanoyl-DL-homoserine lactone at a low concentration of 10 M permitted an increase in the microbial recovery of heterotrophic bacteria from the central Baltic Sea (146). The concept of mutualism between bacterial species emerged and was significantly highlighted by the role of siderophores (147)(148)(149). D'Onofrio et al identified 5 new acyldesferrioxamine siderophores isolated from Micrococcus luteus KLE1011, permitting the culture of a substantial number of marine bacterial species previously considered to be uncultivable (147).…”
Section: Signaling Compoundsmentioning
confidence: 99%
“…Here, siderophores, metal chelators produced by beneficial microbes in response to Fe scarcity, play a role in depriving pathogens of Fe, as well as in availing plants with Fe and other metallic micronutrients (Kloepper et al 1980;Lim and Kim 1997;Vansuyt et al 2007;Dimkpa et al 2009Dimkpa et al , 2015a. This role is the basis for the use of siderophoreproducing bacteria, or siderophores extracted from bacteria, as biofertilizers to supply Fe to plants (Fernandez et al 2005;Radzki et al 2013). In contrast to Fe, Zn may act both directly and indirectly in plant-pathogen systems.…”
Section: Physiological Roles and Roles In Abiotic And Biotic Stress Mmentioning
confidence: 99%
“…Sin embargo, las plantas no poseen la capacidad de sintetizarlo, además de que el contenido total de fósforo en los suelos promedios es de 0,05 %, y únicamente el 0,1 % del total de fósforo presente en esta matriz está en forma disponible para las plantas, ya que la mayor parte está en forma insoluble como parte de fosfatos de calcio y hierro (Radzki et al 2013). Por lo anterior, se hace conveniente la aplicación de microorganismos solubilizadores de fosfato.…”
Section: Solubilización De Fósforounclassified